Assessment of the agricultural mechanization index in Mexico in the period 1930-2023 - Caballero-García, Marco Antonio; Ramírez-Galindo, Jesús; Chávez-García, José Antonio; Rueda-Barrientos, María Claudia; Juárez-López, Porfirio (Revista Mexicana de Ciencias Agrícolas, 2025)
Agriculture in Mexico is increasingly modern and competitive in international markets, so it plays an important role in the growth and development of the country’s economy. Mexico ranks twelfth in the world in the production of agricultural crops; this growth, among other factors, is due to technological changes derived from agricultural mechanization incorporated in agricultural production units during the last decades. This research aimed to analyze the current level of mechanization of agriculture in Mexico, as well as to update the national agricultural mechanization index for each state based on data from the agricultural census of 2022. The results indicate that the current mechanization index in Mexico is adequate and, in some states, it exceeds the FAO recommendation of 50 ha per tractor. Support programs from the federal and state governments have been the most important factor in achieving an adequate mechanization index. However, a significant number of existing tractors are about to exceed their useful life, so it is necessary to establish appropriate strategies for their renewal.